2013
DOI: 10.1017/s1461145713001314
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of pranlukast on Aβ 1–42-induced cognitive deficits associated with downregulation of cysteinyl leukotriene receptor 1

Abstract: Deposition of extracellular amyloid-β (Aβ) peptide is one of the pathological hallmarks of Alzheimer's disease (AD). Accumulation of Aβ is thought to associate with cognition deficits, neuroinflammation and apoptosis observed in AD. However, effective neuroprotective approaches against Aβ neurotoxicity are unavailable. In the present study, we analysed the effects of pranlukast, a selective cysteinyl leukotriene receptor 1 (CysLT₁R) antagonist, on the impairment of learning and memory formation induced by Aβ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…Leukotriene pathway modifiers, including 5-lipoxygenase inhibitor (zileuton) and CysLT 1 R antagonists (montelukast, zafirlukast, and pranlukast), have been used as anti-asthmatic drugs [11][12][13] . Recently, several studies on CysLT 1 R have focused on its novel pathophysiological role in CNS disorders, such as cognitive impairment [14] , cerebral ischemia [15] , brain trauma [16] and experimental autoimmune encephalomyelitis [17] . We recently reported that CysLT 1 R knockdown in the mouse hippocampus prevented the CMS-induced depressive-like phenotype and neuroinflammation [18] .…”
Section: Acta Pharmacologica Sinicamentioning
confidence: 99%
“…Leukotriene pathway modifiers, including 5-lipoxygenase inhibitor (zileuton) and CysLT 1 R antagonists (montelukast, zafirlukast, and pranlukast), have been used as anti-asthmatic drugs [11][12][13] . Recently, several studies on CysLT 1 R have focused on its novel pathophysiological role in CNS disorders, such as cognitive impairment [14] , cerebral ischemia [15] , brain trauma [16] and experimental autoimmune encephalomyelitis [17] . We recently reported that CysLT 1 R knockdown in the mouse hippocampus prevented the CMS-induced depressive-like phenotype and neuroinflammation [18] .…”
Section: Acta Pharmacologica Sinicamentioning
confidence: 99%
“…Moreover, microglial oxidative and nitrosative stress have been strongly implicated as being essential contributors to the synaptic plasticity disrupting action of Aß (Wang et al, 2004;Vilhardt et al, in press). Although SAS and its metabolites have other actions, in particular antiinflammatory (Chavez et al, 2012), inhibition of the transcriptional regulator nuclear factor-jB (NF-jB) (Wahl et al, 1998;Kaiser et al, 1999;de la Fuente et al, 2014) and antagonism of NMDA receptors (Ryu et al, 2003), such effects are expected to abrogate, rather than facilitate, the inhibition of LTP by Aß (Wang et al, 2004;Wang et al, 2005;Hu et al, 2009;Klyubin et al, 2011;Chen et al, 2014;Tang et al, 2014). Thus a highly likely, but yet to be proven, explanation for the negative effects of SAS in the present experiments is impeding the production of GSH under conditions of microglial oxidative and nitrosative stress, including those caused by Aß (Almaguer-Melian et al, 2000;Steullet et al, 2006;Albrecht et al, 2010;Patten et al, 2013;Vilhardt et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…In bilateral i.c.v. A β 1–42 -injected mice, pranlukast and montelukast reversed the A β 1–42 -induced cognitive deficits associated to inflammatory and apoptotic responses, as evidenced by decreased NF-kB p65, TNF- α , IL-1 β , and caspase-3 in the hippocampus and cortex [125, 132]. Moreover, in other studies, montelukast restores learning and memory function in old rats, in which cognition is compromised and the hippocampus concentrations of 5-LOX transcripts and of leukotrienes were increased [27, 133].…”
Section: Cerebral Localization Of Cyslt Receptorsmentioning
confidence: 99%